2017
DOI: 10.1021/acs.iecr.7b02021
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Energetic Materials: Theoretical Relationships to Detonation Performance and Molecular Structure

Abstract: It has been known for decades that high performances for explosives (as characterized by detonation velocity D, detonation pressure P, or Gurney energy E G) are connected with high impact sensitivities, i.e., low values of the drop weight impact height h 50. This trade-off is theoretically substantiated for the first time. It stems from the primary role of the amount of chemical energy evolved per atom for both performance and sensitivity. Under realistic assumptions, log­(h 50) increases linearly with D –4 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 72 publications
2
93
0
Order By: Relevance
“…While we were able to obtain good learning curves from just the Huang & Massa dataset, to ensure their accuracy we supplemented the Huang & Massa data with 309 additional molecules from the dataset given in the supplementary information of Mathieu et al, which includes detonation velocity and detonation pressure values calculated from the Kamlet-Jacobs equations. 37 A few of the molecules are found in both datasets, but most are unique, yielding a total of ≈ 400 unique molecules. We assume detonation velocity is equivalent to shock velocity in Huang & Massa data.…”
Section: Learning Curvesmentioning
confidence: 99%
“…While we were able to obtain good learning curves from just the Huang & Massa dataset, to ensure their accuracy we supplemented the Huang & Massa data with 309 additional molecules from the dataset given in the supplementary information of Mathieu et al, which includes detonation velocity and detonation pressure values calculated from the Kamlet-Jacobs equations. 37 A few of the molecules are found in both datasets, but most are unique, yielding a total of ≈ 400 unique molecules. We assume detonation velocity is equivalent to shock velocity in Huang & Massa data.…”
Section: Learning Curvesmentioning
confidence: 99%
“…Attempts to correlate impact sensitivity of explosives especially within a certain class (eg, nitromaromatics) with molecular properties have been pursued for different groups. [16][17][18][19][20][21][22] In spite of some skepticism, results of these efforts often have been successful. [23] Given that development of new energetic materials is lengthy and expensive because it relies on experimentation, the possibility of using these correlations to eliminate at early stages of development a poor candidate due to sensitivity issues, for instance, is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43][44][45] Regarding structural factors of the molecules, Mathieu observed that there is a relationship between the sensitivity of nitramines and their energy of dissociation and molecular energy per atom. [16] Politzer and Murray also established quantitative relationships between their sensitivities and some characteristics of the molecular surface electrostatic potentials that reflect the dominant positive central regions, a distinct property of an energetic molecule in contrast with a typical organic molecule. [25,29,46,47] Another approach investigated the relationship between impact sensitivities of nitramines and energy transfer rates.…”
Section: Introductionmentioning
confidence: 99%
“…In one earlier work [91], they chose five featurizations: custom descriptor set (CDS, a vector including 21 customized parameters, like raw counts of carbon and nitrogen), sum over bond (SoB, a vector that contains how many different bonds are presented), Coulomb matrix (CM, coordinates and nuclear charges were transformed to the Coulomb matrix eigenvalue spectra representation, which is invariant of the transformation and rotation of the molecular structure), bag of bonds (BoB, a bag containing the number of occurrence of different bonds), and fingerprinting (it transfers molecular graphs into vector form).The kernel ridge regression (KRR), ridge regression (RR), support vector regression (SVR), random forest (RF), and k-nearest neighbors (KNN) were selected as the ML models. In a later work [94], they also adopted LASSO regression, Gaussian process regression (GPR), and neural network (NN) to develop prediction models using the same dataset, plus additional 309 molecules from another reference [96].…”
Section: Design Of High Energetic Materialsmentioning
confidence: 99%